2(6x-2)=3(5x-5)

Simple and best practice solution for 2(6x-2)=3(5x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(6x-2)=3(5x-5) equation:


Simplifying
2(6x + -2) = 3(5x + -5)

Reorder the terms:
2(-2 + 6x) = 3(5x + -5)
(-2 * 2 + 6x * 2) = 3(5x + -5)
(-4 + 12x) = 3(5x + -5)

Reorder the terms:
-4 + 12x = 3(-5 + 5x)
-4 + 12x = (-5 * 3 + 5x * 3)
-4 + 12x = (-15 + 15x)

Solving
-4 + 12x = -15 + 15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15x' to each side of the equation.
-4 + 12x + -15x = -15 + 15x + -15x

Combine like terms: 12x + -15x = -3x
-4 + -3x = -15 + 15x + -15x

Combine like terms: 15x + -15x = 0
-4 + -3x = -15 + 0
-4 + -3x = -15

Add '4' to each side of the equation.
-4 + 4 + -3x = -15 + 4

Combine like terms: -4 + 4 = 0
0 + -3x = -15 + 4
-3x = -15 + 4

Combine like terms: -15 + 4 = -11
-3x = -11

Divide each side by '-3'.
x = 3.666666667

Simplifying
x = 3.666666667

See similar equations:

| 6y^2+1y-2=0 | | Y=157.5x+50 | | 0.8y=-4 | | [-5/8][-8/15]= | | 1=-1.5+0.5y | | x^4-5x^3-9x^2+45x= | | 1/2+(2/3)(3/4)-(4/5)(5/6)= | | 1/2+(2/33/4)-(4/5)(5/6)= | | -2(7x-1)=-5(3x-1) | | M-2=-7 | | 4b-(8-b)=-6 | | x^2+64y^2= | | -11+n=-19 | | 9x-14+5x=33-x-2 | | 30x+12.5y=200 | | 2v=3.2 | | x^2-10x+2xy-6y=0 | | X+124=72 | | 25t-10=-175 | | -1=-1.5+0.5y | | 16=y+6 | | 6x^2-33x=0 | | x+10x+4=-170 | | 6x^3y-54xy= | | 3x^2-6x=2x^2+6x-7 | | 5.6+1.1x=2.1x | | 5-6c=(-37) | | m=-4,(8,9) | | 7x-43+147-3x=90 | | 2x^3+54x= | | 3d+4=2+36-0.5 | | A(25)=A(9)+(8) |

Equations solver categories